SOME ASPECTS OF STANDARD COSTS. - Balch, John (The Accounting Review, 1934)
Abstract This article discusses some aspects of standard costs. There are many kinds of industry which readily lend themselves to the use of standards and some in which the use of standards is the only practical way by which cost accounting data can be assembled without increasing the cost of production to a prohibitive figure or delaying the production procedure by endless weighings, or counting. This has been recognized for many years and the practical accountant used formulas, or bills of material, or normal averages for years before the present publicity was so brilliantly focused on so-called "Standard Costs." It is unfortunate that profession has used so much salesmanship and so little common sense in amplifying the possibilities of comparison which the use of standards makes possible. The installation of cost methods which will be successful in a given plant must first of all, irrespective of accounting theories, be designed for the use of the particular executives associated with the plant in question.